Single‐molecule quantification of 5‐methylcytosine and 5‐hydroxymethylcytosine in cancer genome. Issue 2 (29th April 2020) - Du, Yang; Wang, Yongyao; Hu, Xiao; Liu, Jiyan; Diao, Jiajie
Abstract: Epigenetic modifications present a great influence on tumorigenesis, and have attracted a growing body of researchers' interests. They deal with genomic information to regulate biological pathways related to tumorigenesis and cancer development, without changing the primary base sequence of DNA. As the most important epigenetic modifications, 5‐methylcytosine (5mC) and 5‐hydroxmethylcytosine (5hmC) are the ones most widely investigated in human cancers. To expand our understanding of the roles of 5mC and 5hmC in cancers, multiple methods have been developed to detect and quantify 5mC and 5hmC. While various detection methods having been reviewed, here we focus on ultrasensitive single‐molecule techniques used in quantifying 5mC and 5hmC, including nanopore sequencing, single‐molecule real‐time sequencing, optical mapping, and single‐molecule fluorescent imaging. Abstract : As 5mC and 5hmC play crucial roles on cancer pathogenesis and development, an increasing number of techniques have been developed to detect and quantify 5mC and 5hmC. In this review, the authors focus on single‐molecule quantitation technologies for 5mC and 5hmC, including nanopore sequencing, single‐molecule, real‐time sequencing (SMRT), optical mapping and single‐molecule fluorescent imaging. The authors believe that it can help readers further understand these ultrasensitive techniques and provide future directions for improving single‐molecule DNA sequencing techniques.